Analisis Pengaruh Faktor Internal Dan Eksternal Terhadap Desain Organisasi (Sektor Perbankan, Teknologi Dan Service Komputer, Outsourcing Dan Koperasi Desa Merah Putih): Penelitian - Rahman , Auliya; Hidayaturrahman , Bamas; Saepul Rohman, Ibnu; Dwi Purwantoro, Rachmad; Edward Utama, Rony (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This research aims to analyze the influence of internal and external factors on organizational design in various sectors, including cooperatives, banking, outsourcing companies, and computer service industries. The research method used is descriptive qualitative with a case study approach through interviews, observations, and documentation. The research results show that internal factors such as human resource competence, organizational culture, and leadership style significantly shape the formal structure of the organization. On the other hand, external factors, especially digital technology developments, government regulations, and economic conditions, force organizations to adopt structures that are more flexible, adaptive, and team-based to maintain competitive advantage in the era of disruption.